EKRANISASI NOVEL IVANNA VAN DIJK KE DALAM FILM IVANNA - Fitri Indah Lestari; Asep Firdaus (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
This research aims to describe the addition of characters and characterizations as well as the setting of the film Ivanna by Kimositamboel. This research uses a qualitative method with a descriptive design. The research data sources used were Van Dijk's Ivanna novel and Ivanna film. This research uses data analysis techniques with listening, reading, and recording techniques, After the data is collected, the researcher reduces the data to sort out important data as a research source, after reducing the data that has been selected, the researcher analyzes the data and draws conclusions. The results showed the addition of nine new characters that were not previously in the novel, namely: Ambar, Dika, Agus, Rina, Artur, Grandpa, Grandma Ani, Grandma Ida, and Yudi. Additions to the Ivanna film also appear in the setting of the place, found four additions to the setting of the place in the Ivanna film, namely:  bus setting, street setting, basement setting, and bathroom setting. Based on this, it can be concluded that the film Ivanna made many additions to the characters and settings in the process of adapting the story from the novel Ivanna Van Dijk, so that the film presented has a new and different feel from the previous story contained in the novel.